2000
DOI: 10.22358/jafs/68083/2000
|View full text |Cite
|
Sign up to set email alerts
|

Effects of early lactation concentrate level and glucogenic feed on feed intake, milk production and energy metabolism in dairy cows and heifers

Abstract: In order to examine the effect of two levels of concentrate and the effect of glucogenic feed (0 1/d (GO) or 1 1/d (Gl)) 16 multiparous and 16 primiparous Friesian cows were used in a factorial 2x2 design. The concentrate levels for multiparous cows were 11 kg/d (CI 1) and 15 kg/d (CI 5) and for primiparous cows 9 kg/d (C9) and 12 kg/d (CI2). The glucogenic feed consisted of propylene glycol, polyols, molasses and niacin. All the animals were offered wilted silage ad libitum. The experimental period started fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…Jugular vein blood samples were taken one week before the expected calving day, and 1, 4 and 8 weeks after calving, before the afternoon feeding at 13:00, for the determination of ␤-hydroxybutyrate (BHB), acetoacetate, glucose, insulin, glucagon and non-esterified fatty acids (NEFA), as described by Kokkonen et al (2000b). Urea (Gutman and Bergmeyer, 1974) and total protein (Weichselbaum, 1946) were determined from plasma.…”
Section: Sampling and Chemical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Jugular vein blood samples were taken one week before the expected calving day, and 1, 4 and 8 weeks after calving, before the afternoon feeding at 13:00, for the determination of ␤-hydroxybutyrate (BHB), acetoacetate, glucose, insulin, glucagon and non-esterified fatty acids (NEFA), as described by Kokkonen et al (2000b). Urea (Gutman and Bergmeyer, 1974) and total protein (Weichselbaum, 1946) were determined from plasma.…”
Section: Sampling and Chemical Analysismentioning
confidence: 99%
“…Furthermore, many of these experiments have commenced 1 to 3 weeks after calving. Our previous early lactation study (Kokkonen et al, 2000b) showed the potential of multiparous cows to increase milk yield with increased concentrate level, when crude protein content of grass silage was low. We have also shown, that rapeseed meal supplementation during late gestation may stimulate voluntary feed intake postpartum (Tesfa et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Faverdin et al (1991) measured a mean substitution rate of 0.61 between silage and concentrate in mid-lactation for grass silage-based diets. The substitution rate during the first weeks of lactation has been documented only in a few papers and the results have been variable (Kokkonen et al, 2000;Ingvartsen et al, 2001). …”
Section: Introductionmentioning
confidence: 99%
“…In their study, the amount of concentrate varied between 3.5 and 10.2 kg/day. In early lactation studies there have been considerable variation in the measured substitution rate (Kokkonen et al, 2000;Ingvartsen et al, 2001). In a study by Kokkonen et al (2000), the substitution rate varied from 0.88 to 0.03 for multiparous cows, and for primiparous cows even the silage intake increased with increased concentrate intake during days 1 to 42 of lactation.…”
mentioning
confidence: 99%
See 1 more Smart Citation